Asas Ketertiban Umum dalam Pelaksanaan Putusan Arbitrase Internasional di Indonesia - A.A. Istri Agung Cintya Anomsari; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Jurnal Preferensi Hukum, 2025)
Settlement of international business disputes is usually resolved through international arbitration, as it is "one of the basic principles of international trade law. However, the execution of international arbitration awards in Indonesia is difficult even though Indonesia has ratified the 1958 New York Convention on the Recognition of Foreign Arbitration Awards. The problem is "How is the procedure for the execution of international arbitration awards in the settlement of business disputes in Indonesia? and How is the implication of the principle of public order on international arbitration awards in the settlement of business disputes in Indonesia?" The research method used is the type of normative research with a statutory and conceptual approach. The results of this study are, the regulation of the procedures for implementing international arbitration awards that must be fulfilled, namely the award must fall within the scope of trade law and not conflict with public order. The award must obtain execution from the Chairman of the Central Jakarta District Court. The implication in the implementation of International Arbitration awards in Indonesia is that there is a cancellation or rejection because it is contrary to the Principle of Public Order. This creates legal uncertainty in the settlement of business disputes through international arbitration.